INTERVENSI FOLICLE STIMULATING HORMONE (FSH) DALAM PROSES REMATURASI INDUK IKAN GABUS HARUAN Channa Striata Blkr DIDALAM WADAH BUDIDAYA - Akhmad Ridha Fani; Untung Bijaksana; Akhmad Murjani (Fish Scientiae, 2019)
Snakehead and other fish species in waters of the swamp doing spawning at the beginning or in the middle of the rainy season. Gonadal maturation process so as to returntime is limited. Aquaculture development is highly dependent on the availability of seeds that meet the timeliness, quality and quantity. The seeds can be produced continuously if supported by the availability of mature broodstock with good quality eggs. Some research about the role of hormones and or the use of stimulants to the success in support of gonad development and spawning, such as; Siam Jambal fish, Pangasius hypophthalmus (Ernawati 1999), Catfish, Clarias batrachus (Zairin et al. 2001), and catfish, Hemibagrusnemurus (Supriyadi 2005). By because they were with potential to take advantage of folicle Stimulating Hormone (FSH) that serves as the control at the start of the reproductive cycle up to ovulation and spermiasi in fish. The aim of this study was to determine the effect ofthe injection folicle Stimulating Hormone (FSH) in the parent rematurisasi catfish. Results from the start 17007-52327 item, 0,63-1,07 mm egg diameter, IGS range of 4, 13 to8.50%, and ranged from 0.86 2.4% IHS. Based on the results of the study injection folicle Stimulating Hormone (FSH) capable shorten rematurasi processing time.